2014
DOI: 10.1212/wnl.0000000000000166
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seizures on stroke outcomes

Abstract: SSP and SDH have different characteristics. SDH indicates a poorer prognosis in patients. Increased awareness of SSP and efforts to prevent SDH may be important in improving outcomes following clinical stroke care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
110
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(124 citation statements)
references
References 35 publications
9
110
4
Order By: Relevance
“…In contrast to previous studies [5,34,35,36], we did not find a relationship between the severity of the stroke and the occurrence of seizures.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous studies [5,34,35,36], we did not find a relationship between the severity of the stroke and the occurrence of seizures.…”
Section: Discussioncontrasting
confidence: 99%
“…Mortality appears to be related more to the severity of the stroke. Our data, however, are in contrast with results from other studies in which patients with a post-stroke seizure had higher morbidity and mortality [35]. However, a more focused analysis of mortality in this population will be the topic of a future article.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Cortical location, larger infarct sizes, and hemorrhagic transformation have been associated with an increased risk for the development of seizures following ischemic stroke [6]. The occurrence of early seizures after ischemic stroke is associated with poor functional outcome and higher mortality [7,8]. Two recent studies have shown an increased risk of seizures (including electrographic seizures) with the presence of epileptiform patterns (including PP) in neurocritical care patients [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…2 On the other hand, epileptic seizures following stroke 3,4 and electrographic seizures and interictal epileptiform discharges in critically ill patients are known to worsen the outcome. [5][6][7] The current International League Against Epilepsy (ILAE) definition of epilepsy 8 allows for the diagnosis of epilepsy after a single unprovoked seizure, provided that there is at least a 60% probability of recurrence, as it is the case of the first unprovoked seizure after the acute stroke phase.…”
Section: Introductionmentioning
confidence: 99%